ZmTE1 promotes plant height by regulating intercalary meristem formation and internode cell elongation in maize. Issue 3 (9th November 2021) - Wang, Fengxia; Yu, Zipeng; Zhang, Maolin; Wang, Mengli; Lu, Xiaoduo; Liu, Xia; Li, Yubin; Zhang, Xiansheng; Tan, Bao‐cai; Li, Cuiling; Ding, Zhaojun
Summary: Maize height is determined by the number of nodes and the length of internodes. Node number is driven by intercalary meristem formation and internode length by intercalary cell elongation, respectively. However, mechanisms regulating establishment of nodes and internode growth are unclear. We screened EMS‐induced maize mutants and identified a dwarf mutant zm66, linked to a single base change in TERMINAL EAR 1 ( ZmTE1 ). Detailed phenotypic analysis revealed that zm66 ( zmte1‐2 ) has shorter internodes and increased node numbers, caused by decreased cell elongation and disordered intercalary meristem formation, respectively. Transcriptome analysis showed that auxin signalling genes are also dysregulated in zmte1‐2, as are cell elongation and cell cycle‐related genes. This argues that ZmTE1 regulates auxin signalling, cell division, and cell elongation. We found that the ZmWEE1 kinase phosphorylates ZmTE1, thus confining it to the nucleus and probably reducing cell division. In contrast, the ZmPP2Ac‐2 phosphatase promotes dephosphorylation and cytoplasmic localization of ZmTE1, as well as cell division. Taken together, ZmTE1, a key regulator of plant height, is responsible for maintaining organized formation of internode meristems and rapid cell elongation. ZmWEE1 and ZmPP2Ac‐2 might balance ZmTE1 activity, controlling cell division and elongation to maintain normal maize growth.